Сборник польской поэзии в русских переводах, составленный Юзефом Чапским в 1942 году: история возникновения, анализ переводов - Biełow, Igor (Colloquia Litteraria, 2019)
“An Anthology of Polish Poetry in Russian Translations”, edited by Józef czapski in 1942, circumstances Surrounding the publication of this Anthology and an Analysis of the Translations This paper deals with An Anthology of Polish Poets edited by Józef Czapski in 1942 in Tashkent, which has not been published yet. The tools of Translation Studies applied here have allowed to analyse the basic translation problems facing the Russian poets when they, on Czapski’s request, translated selected examples of Polish poetry